Computed tomography image-based assessment of mean portal vein diameter in a tertiary hospital of Nepal - Sah, Ramswarth; Koiri, Shivpoojan; Gurung, Ghanshyam; Lal Pradhan, Bijay (Journal of Chitwan Medical College, 2026)
Introduction: The portal vein is the main vessel of the portal venous system. This study aims to assess the mean portal vein diameter (MPVD) of healthy individuals using contrast-enhanced computed tomography and correlate it with age, gender, height, weight, and BMI.Methods: This descriptive cross-sectional study was conducted in the Department of Radiology at Tribhuvan University Teaching Hospital from 6 Mar to 5 Sep 2024, following ethical approval. Inclusion criteria: adults ≥18 years with normal liver on CT for non-hepatic indications. Exclusion criteria: poor image quality, portal vein variants, and incomplete data. MPVD was measured at three levels on 3-mm axial CT images. Data were analysed using SPSS version 27. Independent t-tests, one-way ANOVAs, and Pearson correlations were used. A p-value